The Influence of Leadership, Performance Allowances, and Work Culture on Employee Performance at the Candi District Office - Tri Ardha Rachmadani; Kumara Adji Kusuma; Sumartik Sumartik; Khoong Tai Wai (Dinasti International Journal of Education Management and Social Science, 2025)
This study aims to analyze the influence of Leadership, Performance Allowances, and Work Culture on Employee Performance at the Candi District Office. The method used is quantitative descriptive with a non-probability technique in the form of purposive sampling. The number of respondents was 83 employees of the Candi District Office. The data collection technique used a questionnaire, while the data was processed using the Statistical Program For the Social Sciences software version 27. The results of the study indicate that: (1) Leadership has a positive and significant effect on employee performance; (2) Performance Allowances have a positive and significant effect on employee performance; and (3) Work Culture does not have a significant effect on employee performance at the Candi District Office. The conclusion of the study confirms that leadership and performance allowances are determinants of performance, while work culture in this context does not have a significant impact.